2020
DOI: 10.1634/theoncologist.2020-0491
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Single Arm Pilot Study of the CHK1 Inhibitor Prexasertib (LY2606368) in BRCA Wild-Type, Advanced Triple-Negative Breast Cancer

Abstract: • Monotherapy with prexasertib demonstrated modest activity in BRCA wild-type, recurrent triple-negative breast cancer, highlighting the unmet need for combination treatment strategies. • Neutropenia, anemia, and thrombocytopenia are common with the use of prexasertib but are manageable with supportive care measures. Prophylactic use of granulocyte colony stimulating factor should be considered to avoid dose reductions or treatment delays. • Pharmacodynamic studies showed prexasertib treatment induced DNA dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 20 publications
4
42
0
Order By: Relevance
“…However, the clinical efficacy of prexasertib was modest in advanced BRCA wild-type triple-negative breast cancer, despite similar molecular features with HGSOC (46). The posthoc analysis of HGSOC indicated that prexasertib activity might be associated with CCNE1 amplification and overexpression (45).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the clinical efficacy of prexasertib was modest in advanced BRCA wild-type triple-negative breast cancer, despite similar molecular features with HGSOC (46). The posthoc analysis of HGSOC indicated that prexasertib activity might be associated with CCNE1 amplification and overexpression (45).…”
Section: Discussionmentioning
confidence: 98%
“…In patients who administered BI 2536 or volasertib, neutropenia was the most frequently observed adverse event, and about 30%-40% of the patients experienced grade 3 or 4 neutropenia (23)(24)(25)27,28). Similarly, hematological adverse events were frequently observed in the patients that were treated with prexasertib, and almost all the patients experienced grade 3 or 4 neutropenia (44)(45)(46)(47). Therefore, the hematological toxicity of these drugs should be kept in mind; however, it is important to also note that all clinical trials have concluded the safety profile.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, prexasertib showed modest clinical efficacy in the subsequent phase II trial evaluating nine patients with BRCA-wt recurrent triple-negative breast cancer (TNBC). One patient exhibited PR, and four achieved SD; the median PFS was 86 days [145]. However, the results from a recent phase I study do not favor the combination of prexasertib with ralimetinib (p38 mitogen-activated protein-kinase inhibitor) in advanced or metastatic tumors, as of nine enrolled patients, three experienced serious DLTs G4, and only one patient had the best overall response of SD [147].…”
Section: Chk1 Inhibitors In Clinical Trialsmentioning
confidence: 96%
“…Indeed, prexasertib did well in several trials as a monotherapy, mainly in patients with advanced solid tumors. The monotherapy was tolerated with several DLTs where the most common treatment-related SAE G4 was neutropenia [143][144][145][146]. However, the neutropenia was transient and could be recovered (median duration of six days) without any supporting care [146].…”
Section: Chk1 Inhibitors In Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation